Pengaruh Ice Breaking Terhadap Kesiapan Belajar Peserta Didik Melalui Pembelajaran PJOK Kelas IX di SMPN 28 Surabaya - Faiqotul Himmah Mujahidah; Bambang Ferianto Tjahyo Kuntjoro (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students often experience boredom during learning activities. This is a common thing to happen, especially because they are bored with the material given. Therefore, teachers need to learn the Ice breaking method. Ice breaking is a strategy used to create a conducive and enjoyable learning environment. The aim of this research is to find out how much influence ice breaking has on students' learning readiness. This research uses a classroom action research method using a quantitative descriptive approach. Data was collected via questionnaire. Based on the research results, there is an influence between ice breaking and readiness to learn, this is because ice breaking can stimulate students to be more ready to receive learning.